The Digital Transformation of European Higher Education
XVII, 221 p. 27 illus., 14 illus. in color.
Keywords: This volume analyzes e-learning in European higher education, focusing on the technological, ecological, and social challenges of digital transformation. Started pre-pandemic and a result of an ECOLHE project funded by the European Union's Erasmus+ programme, the book discusses the impact of this global crisis, as well as the need for universities to integrate information and communications technology (ICT) in teaching and learning. The book presents multiple national case studies and examines how European universities adopt ICT for Lifelong Learning (LLL), uphold quality standards, and foster teachers' professional growth. It further sheds light on the translation of e-learning ideals into practical realities within academic institutions. From enhancing digital skills to refining teaching methodologies, the book offers valuable insights for educators, administrators, and policymakers alike. The multidisciplinary approach includes theoretical frameworks, pilot training initiatives, and strategic recommendations, all aimed at strengthening higher education's digital infrastructure. Navigating the challenges of digitalization, the book offers solutions for how European universities can remain resilient against the evolving demands of the modern world.